Answer:
50.8
Explanation:
We can solve by using order of operations or PEMDAS (Parenthesis,Exponents,Multiplication and Division(left to right), Addition and Subtraction(left to right))
We have 4³ - (3 + 2³) · 1.2
==> first we do operations in the parenthesis (do the exponent first as it comes before addition in PEMDAS) (2³ = 2 · 2 · 2)
4³ - (3 + 8) · 1.2
==> we then add 3 and 8 to close the parenthesis
4³ - 11 · 1.2
==> next we evaluate the exponents (4³ = 4 · 4 · 4)
64 - 11 · 1.2
==> next we do multiplication and division going left to right if any
64 - 13.2
==> finally we subtract 13.2 from 64
50.8